2011
DOI: 10.1530/eje-11-0384
|View full text |Cite
|
Sign up to set email alerts
|

Circulating glucagon is associated with inflammatory mediators in metabolically compromised subjects

Abstract: Background: Acute phase mediators promote metabolic changes by modifying circulating hormones. However, there is virtually no data about the link between glucagon and inflammatory parameters in obesity-related chronic low-grade inflammation. Study design: We performed both cross-sectional and longitudinal (diet-induced weight loss) studies. Methods: Circulating glucagon concentrations (ELISA), parameters of glucose and lipid metabolism, interleukin 6 (IL6), and complement factor B (CFB) were analyzed in 316 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Next we found that glucagon stimulated ghrelin secretion and proghrelin mRNA production. Our use of glucagon in the low nanomolar range is representative of the fasting levels of circulating glucagon in humans (20) and has been used by other groups to study the effects of glucagon in vitro (21). The stimulatory effect of glucagon on ghrelin secretion that we observed was also demonstrated in models in which glucagon was directly perfused through the femoral vein (15) or in isolated stomachs (16).…”
Section: Discussionmentioning
confidence: 59%
“…Next we found that glucagon stimulated ghrelin secretion and proghrelin mRNA production. Our use of glucagon in the low nanomolar range is representative of the fasting levels of circulating glucagon in humans (20) and has been used by other groups to study the effects of glucagon in vitro (21). The stimulatory effect of glucagon on ghrelin secretion that we observed was also demonstrated in models in which glucagon was directly perfused through the femoral vein (15) or in isolated stomachs (16).…”
Section: Discussionmentioning
confidence: 59%
“…Commercial ELISAs have LODs of 0.3 to 10 pM (e.g., assays from BioVendor or RayBiotech). This concentration LOD is far lower than the 1 nM achieved here, making them more suitable for serum measurements, where glucagon concentrations are ~50 pM (but highly variable) [31]. In principle it would be possible to incorporate a preconcentration step to improve the concentration LOD of the CEIA.…”
Section: Resultsmentioning
confidence: 95%
“…The studies that have been done show somewhat conflicting results; there may be a trend towards increased glucagon production after malabsorptive procedures. Patients undergoing medical weight loss show decreased glucagon production (109111). After AGB there is no change in glucagon production (68, 91, 93), and after SG there is evidence of both early increase (42, 94) and late decrease (44, 112).…”
Section: Resultsmentioning
confidence: 99%